Brand Image and Promotion of International Coffee Shop’s Consumer Loyalty in Indonesia - Haidar Farid, Muhammad; Indra Wijaksana, Tri (The International Journal of Business Review (The Jobs Review), 2023)
In Indonesia, coffee has become a close part of life among low and high society, with the entry of one of the coffee shops into the coffee industry in Indonesia and International coffee chain being one of them, this factor has a big impact on the lifestyle of people in Indonesia. In consuming Starbuck products, for people who have a high opinion or adequate economy, of course it is easy to buy products from International coffee chain, but for people who have a low income, they might think before buying products from International coffee chain. At this time drinking coffee has become a culture among the public and International coffee chain has succeeded in giving "identity" to its consumers. Therefore, this study aims to examine the effect of brand image and promotion on consumer loyalty at International coffee chain Indonesia. This study uses a quantitative method using a questionnaire as a data collection instrument. The data obtained from 162 respondents were analyzed using several techniques with the aim of testing the relationship between the independent variables brand image (X1) and promotion (X2) on the dependent variable consumer loyalty (Y). The results showed that brand image and promotion simultaneously had a significant influence on consumer loyalty. Therefore, it can be concluded that brand image and promotion have a positive and significant relationship with International coffee chain consumer loyalty in Indonesia. Therefore, this research is expected to encourage International coffee chain to continue to improve the quality and innovation of its products, so that International coffee chain products will be increasingly recognized by consumers and the wider community. However, International coffee chain still has to do more active promotions because the development of advanced technology causes many variations in promotion so that there are many unique and efficient variations for promotion.